The Psychological Complexity of the Main Character in Valerie Patkar's 'Loversation': An In-depth Analysis of Literary Psychology - Nur Ulfah Hidayah; Ratih Dwi Rahmadani (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The personalities of the characters are based on childhood memories resulting in wounds that carry over into adulthood. Through Sigmund Freud's theory, this research seeks to reveal the Id, Ego and Superego of the characters who are affected by painful childhood memories. A descriptive qualitative approach and a textual approach are used to try to translate the psychology of the characters in the novel Loversation by Valerie Patkar. The results of the research tell the story of the characters who have fears as a result of childhood trauma which makes them have a loner ID, don't care about other people because they are afraid of being disappointed, have lingering feelings of hatred, misunderstandings due to fear which backfires. However, they still have an Ego which often conflicts with their Id. Theala didn't care but came again to make sure Dirga didn't commit suicide. From the loneliness that made him feel empty and even forgave Dirga who was guilty. Dirga's ego, which was afraid, became worried due to his bad childhood and suppressed his feelings for Theala. The superegos of the two characters make Theala and Dirga do things they wouldn't normally do. The superego makes Theala express her fear of her father and Dirga who turns out to love her father more than he hates her.